Efficient Scheduling Algorithm toReduce Communication Overhead in Spectrum Sharing Process in Cognitive Radio Networks - Shyamala Bharathi P. (International Journal of Advanced Science and Technology, 2020)
Cognitive Radio Networks (CRN)enables the radio spectrum to be utilized effectively from the power minimization perspective. Energy consumption is one of the prime design requirements for heterogeneous systems.The game theoretic approachis proposedin order to utilize the spectrum efficiently and reduce communication overhead by normalizing the utility value and by the existence of Nash equilibrium strategies. We proposed a heuristic algorithm for channel allocation based on switching power (CASP) by applying Lagrangianformulation that allocates idle frequencies to the cognitive user. SU consume significant energy during the channel switching from former to current frequencies.Proposed scheduling algorithm minimizes the switching power with a maximized throughput performance, fairness and efficiency.To enhance the efficiency of spectrum utilization and reduce communication overhead in spectrum sharing process, we propose a two-stage dynamic spectrum sharing scheme in which cooperative and noncooperativemodelsare analyzed in both stages. The co-operative and non-cooperative game models for the existing Throughput Maximization along with restriction in energy consumption (TMER) problem and channel allocation based on switching power (CASP) problem are analysed.Simulation studies are carried out to show the performance comparison between two modes as well as the system revenue improvement of the proposed scheme compared with a conventional scheme without a virtual price control factor.